2006
DOI: 10.1091/mbc.e05-06-0532
|View full text |Cite
|
Sign up to set email alerts
|

The NADPH Oxidase NOX4 Drives Cardiac Differentiation: Role in Regulating Cardiac Transcription Factors and MAP Kinase Activation

Abstract: Reactive oxygen species (ROS) generated by the NOX family of NADPH oxidases have been described to act as second messengers regulating cell growth and differentiation. However, such a function has hitherto not been convincingly demonstrated. We investigated the role of NOX-derived ROS in cardiac differentiation using mouse embryonic stem cells. ROS scavengers prevented the appearance of spontaneously beating cardiac cells within embryoid bodies. Downregulation of NOX4, the major NOX isoform present during earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 52 publications
14
203
1
Order By: Relevance
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…4F), indicating that an extrinsic source of ROS can signal cardiogenesis in the absence of a mitochondrial signal. Indeed, extrinsic peroxides have been shown to be cardiogenic in various models of stem cell differentiation [15][16][17][18], and hydrogen peroxide (10 lM) was also cardiogenic during differentiation in low glucose (Supporting Information Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The ES cell line R1 was provided by Dr. Sagrario Ortega (CNIO, Madrid, Spain). The CGR8 ES cell line and a clonal derivative containing a ribozyme targeting NOX4 (R19 cell line) were gifted from Dr. Marisa Jaconi (Universite de Geneve, Genève, Switzerland) and have been described previously [18]. The Brachyury-green fluorescent protein (Brachyury-GFP) ES cell line was provided by Dr. Gordon Keller (McEwen Center for Regenerative Medicine, Toronto, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nox4 is necessary for the differentiation of mouse embryonic stem cells or fibroblasts into myocytes [53,54]. In addition, Nox4 may contribute to the pathological activation of cardiac fibroblasts in cardiac fibrosis associated with heart failure [54].…”
Section: B Nox Enzymes In the Myocardiummentioning
confidence: 99%